Two adjacent angles form a resulting angle with measure 160° . m∠1=3x° and m∠2=(2x+10)° . Solve for x . What are the two unknown angles’ measurements?

m∠1=
°, m∠2=
°

7 answers

To solve for x, we can set up an equation based on the given information.

The sum of two adjacent angles is equal to the resulting angle:
m∠1 + m∠2 = 160°

Substituting the given values:
3x + (2x + 10) = 160°

Combining like terms:
5x + 10 = 160°

Subtracting 10 from both sides:
5x = 150°

Dividing both sides by 5:
x = 30°

Now we can find the measurements of the two unknown angles:

m∠1 = 3x = 3 * 30° = 90°
m∠2 = 2x + 10 = 2 * 30° + 10 = 70°

Therefore, the two unknown angles' measurements are:
m∠1 = 90°
m∠2 = 70°
An illustration shows three rays extending from a common origin. The angle measures between them are labeled.An illustration shows three rays extending from a common origin. The angles between them are labeled. The first ray extends vertically upward from the vertex, the second ray is inclined upward from the vertex to the right, and the third ray extends horizontally to the right. The angle between the first and the third rays is marked with a right angle symbol. The angle between the first and the second rays is labeled as left parenthesis x plus 4 right parenthesis degrees. The angle between the second and the third rays is labeled as left parenthesis 3x plus 2 right parenthesis degrees.

What are the two unknown angle measures that form the 90° angle?

(x+4)°=
°, (3x+2)°=
°
The two unknown angle measures that form the 90° angle can be found by setting the given angles equal to 90° and solving for x.

Given:

Angle between the first and the second rays: (x + 4)°
Angle between the second and the third rays: (3x + 2)°

To find x, we set the angle between the first and the second rays equal to 90°:

(x + 4)° = 90°

Now we can solve for x:

x + 4 = 90
x = 90 - 4
x = 86°

Substituting this value of x into the angle between the second and the third rays:

(3x + 2)° = (3 * 86 + 2)°
= 260° + 2°
= 262°

Therefore, the two unknown angle measures that form the 90° angle are:

(x + 4)° = 86° + 4° = 90°
(3x + 2)° = 3 * 86° + 2° = 262°
it says its wrong
I apologize for the error in my previous response. Let's reassess the problem.

Given:

Angle between the first and the second rays: (x + 4)°
Angle between the second and the third rays: (3x + 2)°

We are looking for the two unknown angle measures that form the 90° angle.

One of the angles must be 90°, so we can set up an equation:

(x + 4)° + (3x + 2)° = 90°

Simplifying the equation:

4x + 6 = 90

Subtracting 6 from both sides:

4x = 84

Dividing both sides by 4:

x = 21

Now we can find the two unknown angle measures:

(x + 4)° = 21 + 4 = 25°
(3x + 2)° = 3(21) + 2 = 63 + 2 = 65°

Therefore, the two unknown angle measures that form the 90° angle are:

(x + 4)° = 25°
(3x + 2)° = 65°
thanks man your a life saver
You're welcome! I'm glad I could help. If you have any more questions, feel free to ask.